How to Be a Good Forerunner in Carbon Neutral Trucking - Christina Littlejohn; Stef Proost (Center for Economic Studies and Ifo Institute (CESifo), 2021)
EU countries want to decarbonize their road freight transport quickly. Long-haul electric trucks are a promising technology. There are several competing designs but at present the trade-off is between e-trucks with very large batteries and e-trucks with a smaller battery but combined with motorways electrified via catenary lines. In the latter case a combination of public investment (catenary lines on major motorways) and private investment (electric trucks) is required. As long-haul truck transport is partly international this raises problems of coordination among countries. We study the possible pricing and investment strategy of one forerunner country that faces lagging neighbors. The forerunner can make the use of electric trucks mandatory on its own territory by using very high road charges for diesel trucks. If it has opted for a catenary system, it faces still the choice of how it will price the use of its electric motorways. International diesel trucks, when crossing the border of a forerunner country, have to choose between paying high charges and transferring the load into an e-truck. We study the outcome of this international coordination game exploring the non-cooperative outcome varying the relative size of the forerunner in international truck traffic and varying the cost of electric highways.
Keywords: 330; electric trucks; freight transport; climate policy; tax exporting; distance charging